The Infected Total Knee Arthroplasty Prevention, Diagnosis, and Treatment (Springer International Publishing, 2018)
This book is structured in a way that guides the reader from prevention through to diagnosis and then treatment of infection following total knee arthroplasty, in each case providing state of the art information on available techniques and procedures. The section on the crucial preventive measures include guidance on preoperative optimization and skin preparation, antibiotic prophylaxis, and preoperative microbiological screening. All relevant aspects of diagnosis of infection are considered in detail, and the treatment-related section includes chapters on antibiotic suppression, arthroscopic lavage, open debridement with polyethylene exchange, one- and two-stage revision arthroplasty, and knee arthrodesis as a salvage procedure. Readers will also find clear instruction on how to proceed when all attempts to eradicate infection fail. In reflecting the latest knowledge and practice in this rapidly advancing field, the book will be an asset to all who are involved in the care of these patients. .